Analysis Of The Validity Of Underhand Exchange Agreements (Study Of Court Decision Number 21/PDT.G/2020/PN BLK) - Ayu Ambarwati; Mega Yuni Hospita; Pucuk Nyimas Sekar A.S; Aslan Noor (Warmadewa Press, 2024)
This study aims to analyze the validity of the underhand exchange agreement based on a case study of court decision number 21/Pdt.G/2020/PN BLK. The method used in this study is qualitative with a juridical-normative approach. Data were obtained through in-depth interviews with legal experts and practitioners, as well as document studies of court decisions and relevant legal literature. The analysis was carried out using content analysis and juridical analysis techniques to identify and assess the legal aspects of the underhand exchange agreement and its application in court decisions.The results of the study indicate that the validity of the underhand exchange agreement is greatly influenced by the fulfillment of the requirements for the validity of the agreement according to civil law in Indonesia. The court decision in this case underlines the importance of the elements of agreement and good faith between the parties in ensuring the validity of the agreement. This study also found that although underhand agreements are often considered more vulnerable to legal disputes, court decisions provide important guidance on how such agreements can be legally recognized and enforced.This research contributes to the development of contract law theory, particularly regarding underhand agreements, and provides recommendations for legal practitioners in drafting and handling legally valid exchange agreements.